Integrated Interface Development Environment using STEP Universal Data Structure - M.S. Tg Sulaiman, T; B. Mohamed, S; Minhat, M; S. Mohamed, A; R. Mohamed, A (International Journal of Engineering and Technology, 2018)
Nowadays modern manufacturing demands advanced computer controller, having higher input language and less proprietary vendor dependencies. STEP stands for Standard for the Exchange of Product model data is the next generation of data model between CAD/CAM and CNC system. STEP is still under research and development all around the world. This paper describes the design, development and testing of an integrated Interface development environment for STEP file using Universal Data Structure, which aims to provide support for machining operation.Â  The system also aims to provide function of reading and extracting the relevant information associated with the machining data and to write the G-Code file. The sample of machined block is designed from 3D CAD modeler which consisted of features need to be machined from a blank workpiece and saved in the STEP file format. The validation process will be done using the simulation in the Mach3 software.Â Â